Drought stress recovery of hydraulic and photochemical processes in Neotropical tree saplings. (23rd July 2021) - Manzi, Olivier Jean Leonce; Bellifa, Maxime; Ziegler, Camille; Mihle, Louis; Levionnois, Sébastien; Burban, Benoit; Leroy, Céline; Coste, Sabrina; Stahl, Clément
Abstract: Climate models predict an increase in the severity and the frequency of droughts. Tropical forests are among the ecosystems that could be highly impacted by these droughts. Here, we explore how hydraulic and photochemical processes respond to drought stress and re-watering. We conducted a pot experiment on saplings of five tree species. Before the onset of drought, we measured a set of hydraulic traits, including minimum leaf conductance, leaf embolism resistance and turgor loss point. During drought stress, we monitored traits linked to leaf hydraulic functioning (leaf water potential (ψmd ) and stomatal conductance ( g s )) and traits linked to leaf photochemical functioning (maximum quantum yield of photosystem II ( F v / F m ) and maximum electron transport rate (ETRmax )) at different wilting stages. After re-watering, the same traits were measured after 3, 7 and 14 days. Hydraulic trait values decreased faster than photochemical trait values. After re-watering, the values of the four traits recovered at different rates. F v / F m recovered very fast close to their initial values only 3 days after re-watering. This was followed by ETRmax, Ψmd and g s . Finally, we show that species with large stomatal and leaf safety margin and low πtlp are not strongly impacted by drought, whereas they have a low recovery on photochemical efficiency. These results demonstrate that πtlp, stomatal and leaf safety margin are a good indicators of plant responses to drought stress and also to recovery for photochemical efficiency.